EFFECTS OF COPPER TOXICITY ON DIFFERENT GROWTH ATTRIBUTES OF PHLOX DRUMMONDII - Syeda Fatima (Zibeline International, 2021)
Heavy metal contamination is one of the major problems prevailing in environment. Copper in high concentration is considered to have serious effects on plant growth parameters which results in chlorosis, disturbed mineral uptake and stunted growth. A pot experiment was conducted to evaluate the ability of Phlox drummondii to tolerate and accumulate high copper doses. Plants were exposed to copper toxicity at three different concentrations (10 ppm, 20 ppm and 30 ppm) by using copper sulfate (CuSO4.5H2O). Results showed that chlorophyll-a, chlorophyll-b, total chlorophyll and carotenoids of treated plants decreased significantly (p˂0.05) with the increase of copper concentration. Selected copper levels showed no effect on plant height, number of leaves, leaf area and ascorbic acid (p>0.05). Relative water content increased significantly (p˂0.05) as compared to control plants. Copper uptake by roots of treated plants was greater as compared to control plants indicating Phlox drummondii ability to grow well in the copper contaminated soils and could be classified as copper tolerant plant. Copper tolerance by phlox was associated with its capacity to absorb and accumulate in roots preventing translocation of metal to other photosynthetic tissues. Therefore, Phlox drummondii has the characteristic to be used as hyperaccumulator by vegetating in copper contaminated soils. Further studies at genetic level would play a key role in understanding the tolerance mechanism of Phlox drummondii towards copper contamination.